Evaluating the Impact of Common Non-Oncologic Medication Use During Radiotherapy in Patients with High-Risk Prostate Cancer - Haley K. Perlow; Karishma Khullar; Ritesh Kumar; Sonya Sasmal; Kent Nakamoto; Yevgeniya Gokun; Jacob Eckstein; Rebekah Young; Dayssy A. Diaz; Douglas Martin; Katharine A. Collier; Lingbin Meng; et al. (Current Oncology, 2025)
Introduction: The treatment efficacy of prostate cancer (PCa) radiotherapy (RT) can be inadvertently affected by the concurrent usage of non-oncologic medications. Many studies have associated the intake of several non-oncologic drugs with cancer specific outcomes. In this study, we report the impact of daily non-oncologic medications including aspirin, metformin, and statins on time to progression for patients with high-risk PCa. Methods: Patients with high- and very high risk PCa (NCCN definition of Gleason score ≥ 8, prostate-specific antigen (PSA) ≥ 20, or ≥cT3a) who received definitive RT at two institutions were included in this analysis. Progression was defined as either biochemical (PSA > nadir + 2 ng/mL), locoregional (prostate or lymph nodes, biopsy-proven), or development of distant metastases. Progression-free survival (PFS) was defined as the time elapsed from the start of RT to progression or last follow-up. Cox proportional hazards models evaluated the associations between non-oncologic medications and PFS. Results: There were 237 patients eligible for this analysis, of which 47 (19.8%) and 178 (75.1%) had at least clinical T3 disease or at least Gleason 8 disease, respectively. During RT, 82 (34.6%), 88 (37.1%), and 29 (12.2%) patients were taking aspirin, statin, or metformin, respectively. Overall, 54 patients (22.8%) experienced disease progression. Neither aspirin nor statin usage had a significant association with PFS. Patients prescribed metformin displayed worse PFS compared to patients not taking metformin (aHR: 2.46, 95% CI: 1.06–5.72). Conclusions: Aspirin and statin usage was not associated with likelihood of progression in this large cohort of patients with high-/very high risk PCa. Metformin use was associated with poorer PFS, albeit with a small event rate due to fewer patients taking metformin. Further studies are needed to clarify the impact of common non-oncologic medication use on outcomes for patients with high-risk PCa.